Curriculum Integration: Opportunities to Maximize Assessment as, of, and for Learning - MacMath, Sheryl; Wallace, John; Chi, Xiaohong (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractCurriculum integration, focusing on multidisciplinary tasks/projects relevant to the real-world, lends itself to authentic assessment practices. However, attempting to incorporate assessment of, for, and as learning can be challenging. Using data from two mixed method case studies (n=52, n=27) which tracked middle school student learning throughout separate integrated units, we analyzed the types of assessments used by teachers and the relationship of assessment to student learning. Results and implications for teacher practice are explored.